System analysis of methods of heuristic training of mathematics - Ротаньова, Наталія Юріївна (Pedagogy of Higher and Secondary Education, 2019)
Rotanyova N. Yu. System analysis of methods of heuristic training of mathematics. In the article methods of training of mathematics as one of important components of a methodical system have been examined. Every method of training is described and shown through the variety of heuristic techniques used during its implementation. Among them special place is taken by traditional methods which are complemented by a heuristic component and special heuristic methods.